The Use of Anhydrite (CaO.SO3) for the opacification of low-temperature ceramic Glaze - Prof. Dr. Ahmed Hashim Al-Hindawi (Genius Journals, 2022)
This study attempts to search the effect of anhydrite (CaO.SO3) in the opacification of low temperature glaze as an alternative to the commonly used opacifiers. The hemihydrate gypsum (Plaster of Paris) (CaO.SO3.0.5H2O) was used as a source of anhydrite. Gypsum was added in multiple proportions to two types of alkaline glaze (NaK) and lead (Pb), which were applied to a whiteware body, the samples were burned at two temperatures (900°C and 1050 °C), and two opaque samples were selected for each type of glazes. Several analyses, examinations and calculations were done for analyzing and discussing the results, and it appeared that the cause of the opacity was the optical disturbances resulting from solid particles and gas bubbles suspended in the glazes.
Keywords: Opacity in Glaze; Suspension Particles; Gypsum-Anhydrite